A scheme for throughput maximization in a dual-class CDMA system. - Ramakrishna, S. (IEEE Journal on selected areas in communications)
This work focuses on the problem of efficient exploitation of the available bandwidth in order to provide high bit rates on the wireless link, as will be required in future wireless systems interfacing to broadband fixed networks. In particular, the uplink of a CDMA system with two user classes is considered. One of the classes consists of delay-intolerant users requiring support for a constant information bit rate, while the other consists of delay-tolerant users needing support for an information bit rate larger than a given value. It is assumed that when not transmitting information, synchronization contact is maintained with the base station at a given rate. The objective is to maximize the throughput of the delay tolerant users, while ensuring that the interference to other cells is as low as possible by minimizing the sum of all of the transmit powers used by the mobiles. Two transmission modes for the delay-tolerant users are considered. In the first mode, all of the users are allowed to transmit information when they wish. In the second mode, the transmissions of the delay-tolerant users are scheduled, so that only a limited number of them are transmitting information at any given time instant. It is shown that the second transmission mode, which is a time-scheduled scheme for the delay-tolerant users (with hybrid CDMA/TDMA as a special case), affords a better throughput while imposing the same average power requirements as conventional transmission. The results in this paper can be interpreted using results from previous work based on information theory